OLMs Development to Improve Students’ Ability to Produce Learning Media - Safiah, Intan; Yunus, Muhammad; Ahadin; Mislinawati; Abdar, Yusrijal (International Journal of Emerging Technologies in Learning (iJET), 2023)
This study aims to develop e-learning-based Online Learning Modules (OLMs) suitable for higher education levels, especially for education students. The OLM development combines project learning models with LMS-based e-learning. An OLM can be an innovative learning approach that can assist teachers in delivering online learning during the pandemic. This study employed a research and development approach using an ADDIE model. Based on expert validation, the average score of all indicators fell into a very good category. The result implies that the developed OLMs were feasible to be implemented in a learning setting. After implementation, the students’ perceptions of the modules were also very good. Meanwhile, the study demonstrates that 34% of education students have an excellent ability to produce learning media, 60% have a very good ability, and 6% have good ability. Thus, it is concluded that OLMs could improve the ability of education students to produce learning media.